2020
DOI: 10.1145/3398036
|View full text |Cite
|
Sign up to set email alerts
|

Attribute-based Encryption for Cloud Computing Access Control

Abstract: Attribute-based encryption (ABE) for cloud computing access control is reviewed in this article. A taxonomy and comprehensive assessment criteria of ABE are first proposed. In the taxonomy, ABE schemes are assorted into key-policy ABE (KP-ABE) schemes, ciphertext-policy ABE (CP-ABE) schemes, anti-quantum ABE schemes, and generic constructions. In accordance with cryptographically functional features, CP-ABE is further divided into nine subcategories with regard to basic functionality, revocation, accountabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(53 citation statements)
references
References 110 publications
0
53
0
Order By: Relevance
“…ABE has been shown to have applications in many areas, e.g., electronic health-record (EHR) systems [13] and searchable encryption [14], [15]. However, in public cloud storage, CP-ABE is more practical [16]. Although a variety of protocols [17], [18] have been designed for cloud access control using CP-ABE, many other challenges still exist.…”
Section: Related Workmentioning
confidence: 99%
“…ABE has been shown to have applications in many areas, e.g., electronic health-record (EHR) systems [13] and searchable encryption [14], [15]. However, in public cloud storage, CP-ABE is more practical [16]. Although a variety of protocols [17], [18] have been designed for cloud access control using CP-ABE, many other challenges still exist.…”
Section: Related Workmentioning
confidence: 99%
“…For providing privacy‐aware aggregate authentication, an anonymous certificate‐less aggregate signature scheme 30 was studied. Further, the security services can provide secure communication channels against external attackers, trust management, and privacy issues delt in Zhang et al 31 For further details, one can refer to previous works 28,29,32 …”
Section: Background Knowledgementioning
confidence: 99%
“…The authors [29] have effectively demonstrated the significance of ABE for resource-constrained IoT devices. Some other enhanced CP-ABE schemes [30] with variant features include attribute based proxy re-encryption [7,31], accountable CP-ABE [32], online/offline CP-ABE [5,7] and outsourced CP-ABE [33].…”
Section: Related Workmentioning
confidence: 99%